TECHNOLOGICAL ABSORPTIVE CAPACITY AND DEVELOPMENT STAGE: DISENTANGLING BARRIERS TO RICHES. (10th September 2021) - Fuentes, J. Rodrigo; Mies, Verónica
Abstract : Adoption of better technologies is a crucial way for developing countries to close productivity gaps with leading economies. However, the possibility of growing through technological adoption depends decisively on the country's absorptive capacity. We build a theoretical model of technology adoption that focuses on four factors that shape the countries' technological absorptive capacity, namely: (i) years of education; (ii) quality of the educational system; (iii) barriers that impede the entry and exit of firms; and (iv) the institutions that enhance or impede the diffusion of new technologies. We calibrate the model for a sample of 86 economies. The USA is our benchmark leading economy. We disentangle the relative weight of each development factor in explaining per capita income differences and study patterns in relationships between the type of development barrier and the level of development. Our results show that in relative terms, years of education and education system quality along with high barriers to opening new firms are the main impediments that middle- to high-income economies face in closing the gap with the USA. Education as a whole (quality plus years of education) explains 50% of the gap between high-income countries (HICs) and the USA, while the entry costs account for nearly 25% of this gap. A remarkable result is the small effect that individual reforms have on steady-state productivity in low-income countries (LICs). Outside of institutional framework, the remaining three factors are individually responsible for less than 15% of the gap. This result is explained by poor global absorptive capacity that reduces the effect of each factor when implemented individually. In fact, there are significant nonlinearities between development level and the effects of individual reforms, which are due to the strong complementarities between the different development factors.